Modified Long-Axis In-plane Technique for Radial Artery Cannulation in Children: A Randomized Controlled Trial - Yu, Liu; Zhong, Heying; Jiang, Yan; Zhang, Wangping; Liu, Zhiwei (Frontiers in Medicine, 2022)
Background：The radial artery catheterization is a challenge for anesthetists in pediatric population. The purpose of this study was to determine whether modified long-axis in-plane (MLAX-IP) technique increased the success rate of radial artery catheterization in children. Methods: Eighty children who required arterial catheterization were randomly divided into the MLAX-IP group and dynamic needle tip positioning (DNTP) group (40 cases in each group). Radial artery catheterization was performed with MLAX-IP technique or DNTP technique. Results The first-attempt cannulation success rate was higher in the MLAX-IP group than in the DNTP group (95% vs 80%，P=0.043). The imaging time of artery in the MLAX-IP group was longer than in the DNTP group (19.1 ± 3.1vs 9.6 ± 2.4 s, P<0.001). While the total catheterization time was similar between the 2 groups (88.1 ± 23.0 vs 86.9 ± 46.1s, P=0.475). Conclusion The first-attempt cannulation success rate with MLAX-IP technique is increased, while the total catheterization time is similar between the 2 groups and puncture-related complications are fewer.